Facile synthesis of CuO/CdS heterostructure photocatalyst for the effective degradation of dye under visible light - Hossain, Sk Safdar; Tarek, Mostafa; Thurga Devi, Munusamy; Karim, Kaykobad Md. Rezaul; Roopan, Selvaraj Mohana; Sarkar, Shaheen M.; Cheng, C. K.; Khan, Maksudur R. (Elsevier Ltd, 2020)
In this work, the photocatalytic property of p-type CuO was tailored by creating a heterojunction with n-type CdS. The CuO/CdS nanocomposite photocatalyst was synthesized by the ultrasound-assisted-wet-impregnation method and the physicochemical and optical properties of the catalysts were evaluated by using N2 physisorption, X-Ray Diffraction (XRD),X-Ray Photoelectron Spectroscopy (XPS), Raman spectroscopy, Transmission electron microscopy (TEM), Energy dispersive X-Ray (EDX) mapping, Field Emission Scanning Electron Microscope (FE-SEM), UV–Vis and photoluminescence spectroscopy experiments. Detailed characterization revealed the formation of a nanocomposite with a remarkable improvement in the charge carrier (electron/hole) separation. The photocatalytic degradation efficiencies of CuO and CuO/CdS were investigated for different dyes, for instance, rhodamine B (RhB), methylene blue (MLB), methyl blue (MB) and methyl orange (MO) under visible light irradiation. The obtained dye degradation efficiencies were ~93%, ~75%, ~83% and ~80%, respectively. The quantum yield for RhB degradation under visible light was 6.5 × 10−5. Reusability tests revealed that the CuO/CdS photocatalyst was recyclable up to four times. The possible mechanisms for the photocatalytic dye degradation over CuO/CdS nanocomposite were elucidated by utilizing various scavengers. Through these studies, it can be confirmed that the conduction band edges of CuO and CdS play a significant role in producing O2−. The produced O2− degraded the dye molecules in the bulk solution whereas the valence band position of CuO acted as the water oxidation site. In conclusion, the incorporation of CuO with CdS was demonstrated to be a viable strategy for the efficient photocatalytic degradation of dyes in aqueous solutions.